A Review of Tunable Wavelength Selectivity of Metamaterials in Near-Field and Far-Field Radiative Thermal Transport - Tian, Yanpei (Materials (Basel), 2018)
Radiative thermal transport of metamaterials has begun to play a significant role in thermal science and has great engineering applications. When the key features of structures become comparable to the thermal wavelength at a particular temperature, a narrowband or wideband of wavelengths can be created or shifted in both the emission and reflection spectrum of nanoscale metamaterials. Due to the near-field effect, the phenomena of radiative wavelength selectivity become significant. These effects show strong promise for applications in thermophotovoltaic energy harvesting, nanoscale biosensing, and increased energy efficiency through radiative cooling in the near future. This review paper summarizes the recent progress and outlook of both near-field and far-field radiative heat transfer, different design structures of metamaterials, applications of unique thermal and optical properties, and focuses especially on exploration of the tunable radiative wavelength selectivity of nano-metamaterials.